The Analysis of Women's Boarding Houses Impact on Environmental Sanitation and PHBS in Kampung Baru, Bandarlampung - Erni Oktaviani; Nugraheni Irma Lusi; Istiawati Novia Fitri; Utami Rahma Kurnia Sri (Jurnal Geografi : Media Informasi Pengembangan dan Profesi Kegeografian, 2026)
The increasing number of women’s boarding houses in the Kampung Baru neighbourhood an area surrounding a university has led to a rise in domestic activities that could potentially cause environmental sanitation issues, such as waste management, clean water availability, and the cleanliness of boarding house facilities. Suboptimal sanitation conditions can affect the residents’ adoption of Clean and Healthy Living Practices (PHBS). Previous studies have mostly examined environmental sanitation or PHBS separately; consequently, research on the relationship between women’s boarding houses, environmental sanitation, and PHBS within a single research model remains limited. Therefore, this study aims to analyze the influence of women’s boarding houses on environmental sanitation and their impact on PHBS in Kampung Baru Subdistrict.Penelitian ini menggunakan pendekatan kuantitatif dengan metode Structural Equation Modeling (SEM) tipe Reflective–Reflective Higher Order Construct menggunakan SmartPLS 3.0. Sampel penelitian berjumlah 91 penghuni rumah kost wanita. Data primer diperoleh melalui observasi, wawancara, dan kuesioner skala Likert, sedangkan data sekunder diperoleh dari data jumlah rumah kost dan sumber literatur terkait. Analisis dilakukan melalui uji validitas, reliabilitas, evaluasi model, PLS Algorithm, dan pengujian hipotesis.The results of the study indicate that women’s boarding houses have a highly significant effect on environmental sanitation (t-statistic 10.516; p-value 0.000; F-square 1.077). Environmental sanitation has a highly significant effect on PHBS (t-statistic 7.925; p-value 0.000; F-square 0.528), while women’s boarding houses have a significant effect on HBS (t-statistic 2.552; p-value 0.011; F-square 0.089). The R-squared values of 0.518 and 0.659 indicate that the models effectively explain the relationships among the variables. This study concludes that improving sanitation quality and implementing integrated boarding house management play a crucial role in promoting better PHBS and should serve as a consideration for boarding house managers and local governments in enhancing the quality of the residential environment.